Efektivitas Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Pasca Pengalihan Kewenangan Pemungutan Daerah Provinsi Sumatera Barat - Fithrina, Hendria; Gusminarti, Gusminarti; Hardi, Luthfia Febrina (Nagari Law Review, 2025)
Law No. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments regulates that the authority to collect Rural and Urban Land and Building Taxes is transferred from the Central Government to the Regional Government (Regency/City). This research is entitled The Effectiveness of Rural and Urban Land and Building Tax Collection (PBB P2) After the Transfer of Collection Authority to the Regions in West Sumatra Province. The aim of this research is to determine the effectiveness of Land and Building. Tax collection Rural and Urban in Padang City Bapenda. This type of research is empirical juridical with a qualitative approach. The source of data obtained is primary data with data collection methods through interviews and documentation. The results of the research obtained that the effectiveness of the Rural and Urban Land and Building Tax collected by the Padang City Bapenda is quite effective. That is, with an average of 80%. In 2019 the achievement value was 84.53%, in 2020 the achievement value was 83.06%, in 2021 the achievement value was 85.95%. In 2022 the achievement value was 87.35%. Furthermore, the results of research using descriptive show that the system and procedures for collecting Land Tax and The building is running as it should, but when it comes to paying the Land and Building Tax itself, taxpayers are still reluctant to make direct deposits to the designated Bank or Post and Giro Office and generally taxpayers tend to wait for the collection officer to make the collection.